Treatment of functioning pituitary macroadenoma with endoscopic transsphenoidal surgery: a case report - Agusni Agusni; Willy Adhimarta; Andi Asadul Islam; Djoko Widodo; Nasrullah Nasrullah; Andi Ihwan; Prihantono Prihantono; Muhammad Faruk (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2021)
Pituitary macroadenomas are benign tumors in the pituitary gland measuring more than 1 cm in diameter. Pituitary adenomas account for 8 to 10% of all intracranial tumors and occur primarily in the anterior pituitary lobe and rarely in the posterior lobe. Most pituitary macroadenomas are non-functioning tumors, which show clinical symptoms due to tumor pressure and do not increase hormonal activity. In this case, a 40 y.o. woman was diagnosed with a pituitary macroadenoma after showing clinical symptoms of a functioning tumor, namely acromegaly, prognathism, and large, beefy hands and feet, for the past 4 years. Complaints were accompanied by amenorrhea, intermittent cephalgia, and hemianopsia in the right eye. Blood laboratory tests revealed increased levels of prolactin and growth hormone, while the results of computed tomography (CT) scans and magnetic resonance imaging (MRI) of the head indicate the presence of a pituitary macroadenoma. Endoscopic transsphenoidal surgery, a minimally invasive procedure, was performed with minimal complications.